Drip Irrigation to Increase Hedgerow Fruit Trees Growth of Alley Cropping in Highland Rainfed Agricultural System - Surbkar, Rawin (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 3 (2014): September-December 2014, 2014)
Drip irrigation system was applied in combination with the alley cropping to solve the problem of fruit tree damage during the dry season, increase water use efficiency and productivity of the hedgerow-fruit trees planted on sloping highland rainfed agriculture. Drip irrigation was designed on the basis of engineering principle with low cost investment and high efficiency system. Rainwater was collected in the cylindrical containers set at the upper top part of the experimental plots. Watering from the drip irrigation system was supplied to each planting pit under gravitational force. The amounts of water collected and supplied to each fruit tree were calculated on the basis of the actual water use or evapotranspiration of the fruit tree in the hedgerows during the dry season (January-May). In addition, hydrophilic polymer was also applied to increase the water holding capacity within the root zone before drip irrigation experiment. The experiment was designed as a completely randomized design (CRD) with four replications of 4 practices, (i) non-irrigation, (ii) non-irrigation with polymer using, (iii) drip irrigation and (iv) drip irrigation with polymer using. The effects of drip irrigation on total stored soil water, plant growth and some soil properties were compared with the effects of non-irrigation and polymer application. The results showed that drip irrigation gave substantially higher amount of stored soil water within 1 m soil depth than that of the non-irrigation. However, combination effect of drip irrigation and hydrophilic polymer tended to give the highest stored soil water throughout the experimental periods compared to either drip irrigation or non-irrigation only. During the dry season, the stored soil water under drip irrigation was significantly increased whilst it was decreased under non-irrigation. Fruit trees without drip irrigation were withered and some were died. The results also showed that the plant canopy and height of fruit trees under drip irrigation were growing better than those without irrigation. Vegetative growth of mango, lemon, star apple, guava and sapodilla under drip irrigation were higher than those under non-irrigation at 32, 80, 38, 55 and 20%, respectively. Therefore, the drip irrigation for fruit trees during the dry season, using the rainwater harvested in the rainy season, could be the best strategy for decreasing fruit tree damage and increasing the growth rate excellently which enhances the efficiency of cultivation on sloping land to conserve soil, water and environmental sustainability. Keywords: drip irrigation, alley cropping, hydrophilic polymer
Keywords: drip irrigation, alley cropping, hydrophilic polymer